Organizational Time: a Dialectical View - Pina e Cunha, Miguel (2019)
We present twelve propositions constituting a contribution to a contingency view of time in organizations and synthesize apparently opposite perspectives of time. To articulate them, we relate the ‘planning’, ‘action’ and ‘improvisation’ strategic orientations to the ‘dependent’, ‘independent’ and ‘interdependent’ perspectives of the environment. Then, we relate these strategic orientations related to approaches to the problems of scheduling, synchronization and time allocation. ‘Action’ strategies rely on event time to handle scheduling, use entrainment to synchronize with their environment and view time as linear. ‘Planning’ strategies use even time to handle scheduling, impose their internal pacing upon the environment and view time as cyclic. ‘Improvisation’ strategies use ‘even-event’ time to handle scheduling, synchronize via ‘internal-external’ pacing and hold a spiral view of time. Our argument strengthens the case for a more deliberate approach to time in organizations and favors a dialectical view of organizational phenomena.